Characterization and calibration of a triple-GEM detector for medical applications (2019)
This project aimed to characterize and calibrate the triple Gas Electron Multiplier (triple-GEM) detector owned by the CRYOMAG research group at Universidad Nacional de Colombia, as well as to determine its possible applications in medical dosimetry. The detector's response to various sources of radiation was characterized in terms of amplitude, duration, shape, and polarity of pulses, as well as its efficiency, gain, energy resolution, and temporal resolution. The triple-GEM detector's energy proportionality was calibrated using the spectrum of an Iron-55 radioactive source. Then, the detector was used to measure radiation doses from this source using four different methods, as well as the dose from a medical portable X-ray machine at varying peak tube voltages and tube currents. Obtained doses were compared to reference values. The characteristic properties of the detector were found to be an energy resolution of 19.5%, a temporal resolution of at least 40ns, and a maximum gain of 5E6. For the dose measurements, a calibration coefficient of 1.13E4 was obtained against the respective reference values of each source of radiation. There was a good agreement between the four dose-measuring methods for the Fe-55 source. It was concluded that the triple-GEM detector can be reliably used as a dosimeter, especially for nuclear medicine applications.